Teori Linguistik dalam Pembelajaran Bahasa Arab - Agustina Suryani; Mutiara Islami Uvaradzikri; Muhammad Fadil Uzmi; Sakholid Nasution (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The purpose of this research is to provide an overview of modern linguistics. Descriptive qualitative research methodology is used here. The literature on contemporary linguistics served as the study's data source. The method of data analysis is linguistic content analysis. both current and broad linguistics. According to the study's findings, modern linguistics is the scientific study of language itself, including its lexical, grammatical, and phonological structure (langue) as well as its use as speech (parole). The constituent elements of language—phonology, morphology, syntax, and semantics—are the focus of contemporary linguistic research. In order for language to be used effectively, modern linguistics seeks to better comprehend its nature, phenomena, and constituent parts to interact with others within a social setting.Sociolinguistics, contrastive, and psycholinguistics are some of the advantages of using linguistic theory in Arabic instruction. In order to establish learning objectives and provide an explanation of the language, linguistics is a crucial component of Arabic language instruction Teachers benefit from linguistics' ability to describe and analyse language, which enhances the educational process. Planning maturity is the first step in an effective learning process and is essential to attaining the best learning outcomes. Achieving the objectives of Arabic language instruction begins with careful planning.